Sosialisasi Literasi Pengelolaan Keuangan Bagi Remaja pada Yayasan Hikmat Berkarya Mandiri - Suhardoyo Suhardoyo; A Sudrajat; Roydawaty Bunga Sihol (Jurnal Kabar Masyarakat, 2024)
Low financial literacy among adolescents can have long-term impacts on their future financial decisions. They argue that effective financial education from an early age can reduce the likelihood of poor financial behavior, such as excessive debt and inadequate retirement planning. One of the insights that must be possessed is about financial literacy. Financial literacy education is an important thing that must be given to children, so that they do not become a consumptive generation. Directing children to manage their finances properly is one of the important goals in financial literacy education. Financial literacy education also has a long-term goal, namely to increase children's insight and literacy skills, or from previously lacking literacy to understanding the concept of financial literacy, in addition literacy education also aims to increase awareness of the presence of financial institutions in the midst of society. Community Service with the theme of Socialization of Financial Management Literacy for Adolescents at the Hikmat Berkarya Mandiri Foundation. So that by holding this Community Service activity, it is hoped that it will be able to provide positive knowledge about financial management for Adolescents. This activity will be carried out in the office space of the Hikmat Berkarya Mandiri Foundation, Bekasi with the address Perum Alamanda Regency BC 09 No. 18 RT. 12 RW. 21 Karangsatria Village, Tambun Utara District, Bekasi Regency, West Java. This Community Service activity will be held face-to-face (offline). The output of this Community Service activity is an article in electronic mass media and documentation of the implementation in the form of photos and videos of activities and community service journals.